Sygmoid exteriorization in diverticular perforation.: abdominal reinstatement of the scarred loop. - Perdomo, Roberto; Armand Ugon, César (Cirugía del Uruguay, 1976)
The authors present 4 cases of sygmoid diverticular perforation which were treated in the emergency by exteriorization of the loop, and, in two cases, with later reinstatement of the scarred ioop into the peritoneal cavity. They present the fundaments which led them to choose this technique, and the anatomical and pathological conditions of the process which determine the possibility to apply it. They especially emphasize the necessity to avoid an excission with anastomosis, in the emergency or later, which, according to the personal experience of the authors, and to sorne bibliographical references, is only a preventive measure the risks of which Iargely exceed the common evolutive requirements of the -colonic diverticular disease.